Hypogonadism and low bone mineral density in patients on long-term intrathecal opioid delivery therapy. Issue 6 (1st June 2013) - Duarte, Rui V; Raphael, Jon H; Southall, Jane L; Labib, Mourad H; Whallett, Andrew J; Ashford, Robert L
Abstract : Objectives: This study aimed to investigate the hypothalamic-pituitary-gonadal axis in a sample of male patients undertaking intrathecal opioid delivery for the management of chronic non-malignant pain and the presence of osteopaenia and/or osteoporosis in those diagnosed with hypogonadism. Design: Observational study using health data routinely collected for non-research purposes. Setting: Department of Pain Management, Russells Hall Hospital, Dudley, UK. Patients: Twenty consecutive male patients attending follow-up clinics for intrathecal opioid therapy had the gonadal axis evaluated by measuring their serum luteinising hormone, follicle stimulating hormone, total testosterone, sex hormone binding globulin and calculating the free testosterone level. Bone mineral density was measured by DEXA scanning in those patients diagnosed with hypogonadism. Results: Based on the calculated free testosterone concentrations, 17 (85%) patients had biochemical hypogonadism with 15 patients (75%) having free testosterone <180 pmol/L and 2 patients (10%) between 180 and 250 pmol/L. Bone mineral density was assessed in 14 of the 17 patients after the exclusion of 3 patients. Osteoporosis (defined as a T score ≤−2.5 SD) was detected in three patients (21.4%) and osteopaenia (defined as a T score between −1.0 and −2.5 SD) was observed in seven patients (50%). Five of the 14 patients (35.7%) were at or above the intervention threshold for hip fracture. Conclusions: This study suggests an association between hypogonadism and low bone mass density in patients undertaking intrathecal opioid delivery for the management of chronic non-malignant pain. Surveillance of hypogonadism and the bone mineral density levels followed by appropriate treatment may be of paramount importance to reduce the risk of osteoporosis development and prevention of fractures in this group of patients.